2018
DOI: 10.1111/ijd.13907
|View full text |Cite
|
Sign up to set email alerts
|

IgG from atopic dermatitis patients induces IL‐17 and IL‐10 production in infant intrathymic TCD4 and TCD8 cells

Abstract: IgG of AD patients can stimulate cytokine production in infant thymocytes and thus resembles the peripheral profile observed in adults. These findings suggest a novel mechanism that can contribute to AD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…In this context, maternal antibodies may exert a function, but only a few evidences about this hypothesis can be found in the literature. Between then, antibodies inducing clonal deletion of thymocytes was demonstrated years ago and, more recently, a modulatory effect on T cells cytokine production was evidenced in human thymocytes . Until the present moment, no direct evidence of modulatory effects of antibodies on Tregs maturation is described.…”
Section: Discussionmentioning
confidence: 92%
“…In this context, maternal antibodies may exert a function, but only a few evidences about this hypothesis can be found in the literature. Between then, antibodies inducing clonal deletion of thymocytes was demonstrated years ago and, more recently, a modulatory effect on T cells cytokine production was evidenced in human thymocytes . Until the present moment, no direct evidence of modulatory effects of antibodies on Tregs maturation is described.…”
Section: Discussionmentioning
confidence: 92%
“…Extensive literature evidence demonstrates that the immune status of IgG donors may be related to differential modulation of thymic lymphocytes [ 26 , 31 , 45 , 46 ], which has been discussed in the literature since 2014 [ 6 , 47 ]. Among related observations, nonatopic IgG may be related to thymic maturation of lymphocytes with an allergy inhibition-related cytokine profile induced by γδT cells [ 48 ] as well as T CD4+ and CD8+ cells [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thymocyte separation was performed using Ficoll–Paque Plus (GE Healthcare, Danderyd, Sweden) after centrifugation as previously described [ 31 ]. Cell viability was assessed by flow cytometry.…”
Section: Methodsmentioning
confidence: 99%
“…It should also be mentioned that the IgG from AD patients has recently been described as a modulator of thymic TCD4 and TCD8 cells cytokine production, but the investigation of IgG effect in thymic iNKT cells is unprecedented in the literature, requiring further approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Our group had been discussing and demonstrating that IgG antibodies can exert a pivotal role mediating the modulation of lymphocytes cytokine production . In this context, we also demonstrated that IgG purified from atopic dermatitis (AD) patients can favor the production of IL‐17 and IL‐10 by thymic TCD4 and TCD8 cells . This approach collaborates with the elucidation of AD pathogenesis, but other cell populations also matured in the thymus can be related to AD development, including invariant natural killer T (iNKT) cells.…”
Section: Introductionmentioning
confidence: 90%